A self‐configured link adaptation for green LTE downlink transmission - Salman, Mustafa Ismael; Ng, Chee Kyun; Noordin, Nor Kamariah; Mohd Ali, Borhanuddin; Sali, Aduwati (John Wiley & Sons, 2015)
Green deployment for cellular eNodeBs has been proposed recently to save power and reduce the huge amount of carbon dioxide (CO2) emitted by traditional power‐hungry base stations. Green eNodeBs should also be subjected to restrictions on high data rate and quality of service (QoS), which both entail a high level of power consumption. In this regard, this paper addresses the trade‐off between energy efficiency (EE) and spectral efficiency (SE) in both traditional and green long‐term evolution eNodeBs without sacrificing the QoS. EE is proved to monotonically increase with SE in traditional macrocells and quasi‐concave in green macrocells. Accordingly, a new mapping between channel quality indicator and modulation and coding scheme is proposed to address EE–SE trade‐off with the use of a multi‐criteria decision‐making technique. Then, a self‐configured link adaptation (SCLA) algorithm is developed to ensure that the priority weights related to EE and SE are adapted according to network load with the use of real‐time cross‐layer optimization. Simulation results show that the proposed SCLA provides a significant gain in EE and 52% reduction of CO2 while maintaining SE close to the optimal value. Current and next‐generation cellular networks require such interactive techniques in order to be self‐optimised without complex modifications.